¿Es el artículo una unidad pragmática? Acerca de la teoría de la definitud y la referencia - Pawlik, Janusz (Studia Romanica Posnaniensia, 2021)
In this paper I intend to review some theories of the article, paying attention to the relations they establish between reference and +/–definiteness of a noun phrase (NP). The prototypes of +/–definiteness in Spanish are the definite and indefinite articles and NPs determined by them. Nevertheless, the actual reference of a NP depends mostly on its use (a speech act) and varies according to its pragmatic context. Reference and definiteness are mutually related concepts accompanied by pragmatic and semantic implications. I wish to make a critical overview of some proposals in this field of research.